Snowpiercer [videorecording (Blu-Ray)] - Pong, Chun-ho, 1969-; Masterson, Kelly; Evans, Chris, 1981-; Swinton, Tilda; Bell, Jamie, 1986-; Harris, Ed, 1950-; Hurt, John, 1940-2017; Song, Kang-ho, 1967-; Pill, Alison, 1985-; Spencer, Octavia; Beltrami, Marco; Lob, Jacques, 1932-1990 (Anchor Bay Entertainment, 2014)
The film is set in the future (AD 2031) where, after a failed experiment to stop global warming, an ice age kills off all life on the planet except for the inhabitants of the Snowpiercer, a train that travels around the globe and is powered by a sacred perpetual-motion engine. Its inhabitants are divided by class; the lower-class passengers in one of the last cars stage an uprising, moving car by car up to the front of the train, where the oppressive rich and powerful ride.